2x2 + x – 1
⟹ 2x2 + 2x - x – 1
⟹ 2x (x + 1) – 1 (x + 1)
⟹ (x + 1) (2x – 1)
Therefore, the factors of the given polynomial = (x + 1) (2x – 1)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :